Developing English L2 critical reading and thinking skills through the Pisa reading literacy assessment framework: a case study of Thai EFL learners - Surasak Khamkhong, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to investigate the use of the PISA reading literacy assessment framework (PRF) to improve EFL learners’ critical reading and thinking skills. The sample group, selected by the random sampling technique, included 36 EFL learners from a university in Northeastern Thailand. The instruments consisted of 8 PRF-based reading lessons, a 27-item-PRF-based reading test used as a pre-test and a post-test, and a questionnaire of their attitude toward the designed lessons. The statistics used for data analysis were percentage, mean, standard deviation, and a paired sample t-test. The results revealed that before the intervention, the students’ English reading proficiency was low as is evident from their low pre-test scores (M=14.00). They did fairly well for the literal questions (M=6.11), but poorly for the interpretative questions (M=4.89) and the critical questions (M=3.00), respectively. This means that the students could comprehend the texts but they could hardly interpret or evaluate them. However, after the intervention, they could do much better as their post-test scores were significantly higher (M=18.01). They could comprehend (M=6.78), interpret (M=6.00) and evaluate (M=5.25) well. The paired sample t-test results also confirmed this as the students’ post-test scores for overall, literal, interpretative, and critical questions were significantly higher than the pre-test scores at p<0.001. This indicates that after the intervention, their reading skills had improved. In terms of their attitude, most students were satisfied with the lessons and the instruction, particularly because they were given background information of texts and knowledge about different types of the PRF questions. It may thus be concluded that the designed lessons can help improve students’ English critical reading proficiency and may be used as a teaching model for improving EFL learners’ critical reading and thinking skills.